Analogical Arguments for Egalitarianism. (23rd September 2013) - Freiman, Christopher
Abstract Egalitarians sometimes analogize socioeconomic opportunities to starting gates, playing fields, and the results of a lottery. A fair game is one in which all have an equal opportunity to succeed; egalitarians propose that the same is true of a fair society. A second type of argument for egalitarianism appeals to intuitions about the distribution of found resources. A just division of manna discovered on a strange planet seems to be an equal one. Both types of argument share a crucial feature: they concern the once‐off division of a fixed sum of goods. I argue that the most compelling reasons to depart from an equal division of goods derive from the economic activity involved in producing more of those goods, e.g., Pareto improvements due to efficiency gains that result from incentives that encourage production. We cannot conclude that game analogies and found resources cases arbitrate in favour of equality against non‐egalitarian principles because they exclude precisely those considerations that provide the strongest reasons to reject equality.